2015
DOI: 10.1118/1.4938578
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of neutron dose in radiotherapy patients: Which dose?

Abstract: Quality factor can be replaced by the radiation weighting factor in the evaluation of dose equivalent in radiotherapy environments simplifying the practical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…while neutron dose equivalent was used in this study) and (2) different phantoms (lower values are expected when adult phantom is used instead of a pediatric one). Related to (1), Romero‐Exposito et al 54 . showed that in RT environments Q and w T are approximately equal, and thus neutron doses evaluated using both factors are compatible, with differences below 12%.…”
Section: Discussionmentioning
confidence: 98%
“…while neutron dose equivalent was used in this study) and (2) different phantoms (lower values are expected when adult phantom is used instead of a pediatric one). Related to (1), Romero‐Exposito et al 54 . showed that in RT environments Q and w T are approximately equal, and thus neutron doses evaluated using both factors are compatible, with differences below 12%.…”
Section: Discussionmentioning
confidence: 98%
“…It should also be kept in mind that the assumptions of Eq. (20) are not always fulfilled. This concerns, for example, fast neutrons with energies below a few MeV.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The mass (V) of the gas can be derived from the experimentally measured sensitivity, using relationship (19): (19) By combining Eqs. (14) and (19), the absorbed dose in phantom material t can be expressed as: (20) It is worth underlining that two fi nal factors in Eq. 20, i.e.…”
Section: Calibration Of the Chambers And Correlations Between Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…The neutron dose equivalent can be derived using the following equation, as discussed in Romero-Expósito et al. ( 28 ):…”
Section: Methodsmentioning
confidence: 99%